Faktor-Faktor yang Berhubungan dengan Kunjungan Antenatal Care (ANC) di Wilayah Kerja Puskesmas Gandapura - Nurul Huda; Desi Ernita Amru (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Assessment of the implementation of healthservices for pregnant women can be done by looking at the coverage of K1, K4 and K6 (Ministry of Health of the Republic of Indonesia, 2020). According to data from the Indonesian Ministry of Health on Indonesia’s health profile, in 2021 K4 coverage reached 88.8%, showing an increase compared to the previous year. This increase was caused by new adaptations made due to facing the COVID-19 pandemic situation in 2021. Where in the previous year, there were significant restrictions on routine services, including maternal health services. The aim aof this research is to analyze factors related to antenatal care visits in the Gandapura Community Health Center working area. The type of research used is analytical observational research with the research design used being cross sectional. The research was carried out in November-December 2024. The sample is part of the number and characteristics of the population. The number of samples taken was 30 samples. Each data was tested statistically to see whether there was a relationship between the two variables. For the attitude factor with antenatal care visits, the value was p=0.004, for support from health workers with antenatal care visits, the value was p=0.014, while the husband’s support with antenatal care visits was obtained with a value of p=0.042, so it can be concluede that there is a relationship between attitude, staff support and husband’s support with antenatal care visits for pregnant womwn at the Gandapura health center.